Prevalence of peripheral arterial disease in type 2 diabetes mellitus and it’s correlation with carotid intima-media thickness - Palawat, Sandeep S.; Gupta, Vishal K.; Gupta, Ajesh Chandra; Giri, Richa (International Journal of Advances in Medicine, 2022)
Background: Peripheral arterial disease (PAD) is one of the major macrovascular complications of diabetes mellitus (DM) which is largely neglected by clinicians. DM-associated atherosclerosis can lead to complications in all major of vascular beds, including the coronary arteries, carotid vessels, and lower extremity arteries. Aims and objective were to study the prevalence of PAD in patients with type 2 DM and to study the correlation with carotid artery intima-media thickness Methods: Hospital based cross-sectional study was conducted among the 124 patients admitted with type 2 diabetes (age >25 year) from Dec 2019 to Oct 2021 in the various units of department of medicine or surgery, KPS institute, GSVM medical college Kanpur. Color doppler of limbs and carotid artery was done in study population. Results: In our study based on doppler ultrasound, the prevalence of PAD was found in 31 patients (25%) out of 124 with men having a higher prevalence (24 out of 74; 77.4%), as compared to women (7 out of 50; 22.6%) (p=0.020). The mean Carotid IMT (mm) (Average) was 0.82±0.16 in all diabetics. Patients with PAD have more increase in CIMT (0.95±0.12) as compare to non-PAD (0.77±0.15) p<0.001. Conclusions: By using doppler, we found evidence of PAD in 25% of type 2 diabetics (M>>F). Patients with PAD have more increase in CIMT as compare to non-PAD.